Four-plate capacitive power transfer system with different grounding connections. (February 2020) - Zhu, Qi; Zou, Lixiang Jackie; Su, Mei; Hu, Aiguo Patrick
Highlights: A four-plate capacitive power transfer (CPT) system with different grounding connections is studied by taking the mutual coupling between the plates and the ground into consideration. A 4 * 4 mutual capacitance matrix model including the ground capacitances is established to accurately describe the coupling relationship between the four plates and the ground. Eight grounding connections are identified for effective power transfer among fifteen theoretically possible combinations. The electric field distribution and system output performance of a typical CPT system with two pairs of parallel plates are studied for different grounding connections. Abstract: In this paper, a four-plate capacitive power transfer (CPT) system with different grounding connections is studied by taking the mutual coupling between the plates and the ground into consideration. A 4 * 4 mutual capacitance matrix model including the ground capacitances is established to accurately describe the coupling relationship between the four plates and the ground. Based on the proposed model, eight grounding connections are identified for effective power transfer among fifteen theoretically possible combinations. The electric field distribution and system output performance of a typical CPT system with two pairs of parallel plates are simulated for different grounding connections. A practical coupling setup consisting of two pairs of vertically placed parallel 300 mm * 300 mm square aluminum plates is built to verify the modeling and analysis. Both simulation and experimental results show the measured output voltage under different grounding connections are in good agreement with the theoretical results. It has been found that the ground has minimal impact on power transfer when one pair of the coupled transmitter and receiver plates are grounded, and the highest voltage gain and the lowest leakage electric field are also achieved under this grounding connection. However, considering the practicality, grounding one transmitter plate is the most suitable connection.